In Vitro Evaluation of Three Pisum sativum L. Varieties to Partially Replace Soybean and Corn Meal in Dairy Cow Diet - Maria Ferrara; Emanuele D’Anza; Teresa Montefusco; Piera Iommelli; Barbara Piccirillo; Alessio Ruggiero; Alessandro Vastolo (Animals)
Pea (Pisum sativum L.) seeds are valuable feed ingredients due to their high-quality protein and starch digestibility, making them a viable alternative to soybean meal and corn grain. This study evaluated the nutritional value of three commercial pea varieties (Ganster, Peps, and Poseidon) through in vitro trials. Each variety was incorporated into an experimental diet (GNS, PES, and PNS) for dairy cows, partially replacing soybean and corn meals. These diets were compared to a control diet containing only soybean and corn meals. All diets were incubated anaerobically for 120 h with dairy cow rumen liquor. Results showed that GNS and PES diets enhanced protein degradability (p < 0.05) and fermentation kinetics (p < 0.001). Additionally, all experimental diets reduced ammonia production (p < 0.001), while the PES diet increased (p < 0.001) volatile fatty acid production. Among the tested varieties, Peps demonstrated the greatest potential by improving protein metabolism and volatile fatty acid production. These findings suggest that pea grains can be a suitable alternative in dairy cow diets, supporting efficient ruminal fermentation and nutrient utilization.